An Analysis of Students’ Ability in Reading Comprehension by Using Barrett’s Taxonomy at English Department Universitas Negeri Padang - Liza Purnamasari; Edi Trisno (Universitas Negeri Padang, 2022)
This research was aimed to analyze students' ability in reading comprehension using Barrett's taxonomy at English Department Universitas Negeri Padang. The population of this research was students of the 2018 Academic Year English Education study program who had taken reading classes ranging from Basic Reading, Intermediate Reading, Advanced Reading, Critical Reading, and Extensive Reading. The sample of this research study was 28 students using a simple random sampling technique. This research used a reading comprehension test to obtain data. This research used Barrett's taxonomy as an indicator consisting of five levels, namely: Literal, Reorganization, Inferential, Evaluation, and Appreciation. This research is a descriptive study with a quantitative approach that uses tests as instruments. The results of this study indicated that the students' ability in reading comprehension is in the poor category with a mean score of 53.86. This research showed that students have low ability in understanding the evaluation with a total average score of 31.79%. In addition, the highest percentage is in appreciation comprehension with an average score of 56.55%. Therefore, lecturers are expected to be able to improve students' ability in reading comprehension, especially in understanding the evaluation and reorganization by providing a lot of practice both inside and outside the classroom.